EXPLORING THE IMPACT OF COGNITIVE, AFFECTIVE, AND PERSONALITY DIFFERENCES ON LEARNING PROCESSES - Qalandarova Sabohat Atabekovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Individual differences play a critical role in shaping how learners engage with and internalize new information during various stages of the learning process. This study  investigates  the  extent  to  which  cognitive,  affective,  and  personality-related individual differences predict distinct learning processes—namely encoding, rehearsal, elaboration, and metacognitive regulation. Employing a mixed-methods design, 180 undergraduate  participants  completed  standardized  measures  of  working  memory capacity, cognitive style, learning motivation, and trait anxiety. Quantitative data were analyzed using structural equation modeling to examine direct and indirect effects of individual  differences  on  learning  outcomes.  Complementing  this,  think-aloud protocols  from  a  purposive  subsample  of  30  students  were  thematically  coded  to identify  strategy  use  during  problem-solving  tasks.  Results  reveal  that  (a)  higher working memory capacity and reflective cognitive styles are positively associated with deeper elaboration strategies, (b) intrinsic motivation and low anxiety levels predict more  frequent  metacognitive  monitoring  and  regulation,  and  (c)  personality  traits linked  to  conscientiousness  moderate  the  relationship  between  cognitive  style  and rehearsal strategies. Qualitative themes illustrate how learners adapt their study tactics in  real  time,  confirming  and  extending  the  quantitative  model.  These  findings underscore  the  necessity  of  tailoring  instructional  design  to  accommodate multidimensional  individual  differences,  suggesting  that  adaptive  scaffolding  and metacognitive  prompts  can  enhance  learning  efficiency.  Implications  for  educators include integrating diagnostic assessments of learner profiles and embedding process-oriented interventions to foster self-regulated learning.